Emergent rhombus tilings from molecular interactions with M-fold rotational symmetry - Whitelam, Stephen; Tamblyn, Isaac; Garrahan, Juan P.; Beton, Peter H. (American Physical Society, 2015)
We show that model molecules with particular rotational symmetries can self-assemble into network structures equivalent to rhombus tilings. This assembly happens in an emergent way, in the sense that molecules spontaneously select irregular fourfold local coordination from a larger set of possible local binding geometries. The existence of such networks can be rationalized by simple geometrical arguments, but the same arguments do not guarantee a network’s spontaneous self-assembly. This class of structures must in certain regimes of parameter space be able to reconfigure into networks equivalent to triangular tilings.